The Effect of Yoga Exercise on Reducing Dysmenorrhea Pain Among Adolescent Girls at SMK Negeri 1 Cibatu - Gina Aulia; Nova Rati Lova; Shinny Ria Pratiwi (Public Health Journal, 2026)
Background: Dysmenorrhea is a common menstrual complaint experienced by adolescent girls and may interfere with learning activities and daily activities. Yoga exercise is a non-pharmacological approach that may help reduce pain through relaxation, breathing regulation, reduced muscle tension, improved circulation, and the body's analgesic response. Objective: To determine the effect of yoga exercise on reducing dysmenorrhea pain among adolescent girls at SMK Negeri 1 Cibatu. Methods: This quantitative study used a pre-experimental one-group pretest-posttest design. The sample consisted of 30 adolescent girls who experienced dysmenorrhea and were selected using purposive sampling. Pain intensity was measured using the Numeric Rating Scale before and after the intervention. Data were analyzed using univariate analysis and the Wilcoxon Signed Ranks test. Results: Before the intervention, 17 respondents (56.7%) experienced severe pain, 10 respondents (33.3%) experienced moderate pain, and 3 respondents (10.0%) experienced mild pain. After yoga, 11 respondents (36.7%) reported no pain, 11 respondents (36.7%) reported mild pain, and 8 respondents (26.7%) reported moderate pain. No severe pain was observed after the intervention. The mean pain score decreased from 2.57 to 0.90, and the Wilcoxon test showed p=0.000. Conclusion: Yoga exercise had a significant effect on reducing dysmenorrhea pain intensity among adolescent girls.